2009
DOI: 10.1364/oe.17.009226
|View full text |Cite
|
Sign up to set email alerts
|

Generation of broadband two-dimensional multicolored arrays in a sapphire plate

Abstract: Broadband 2-D multicolored arrays with more than ten periodic columns and more than ten rows were generated in a sapphire plate using two crossed femtosecond laser beams overlapping in time and space. These multicolored 2-D arrays were sensitive to rotation of the sapphire plate in the plane normal to the incident beams. The broadband spectrum, pulse duration less than 40fs, and less than 1%RMS power stability of the array signals make them well suited for various applications, for example multicolor pump-prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 24 publications
2
21
0
2
Order By: Relevance
“…The phase-matching condition of CFWM has also been discussed and used to explain the generation of multicolored sidebands with two noncollinear pump laser pulses [60]. Our experiment has shown that more than 15 spectral upshifted sidebands and two spectral downshifted pulses can be obtained with a spectral width broader than 1.8 octaves, covering the range from UV to near-IR [55][56][57]59,60]. The spectra of the multicolored sidebands can also be tuned in the broadband spectral range by adjusting the cross-angle of the two pump beams or simply by replacing the nonlinear media [59,60].…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…The phase-matching condition of CFWM has also been discussed and used to explain the generation of multicolored sidebands with two noncollinear pump laser pulses [60]. Our experiment has shown that more than 15 spectral upshifted sidebands and two spectral downshifted pulses can be obtained with a spectral width broader than 1.8 octaves, covering the range from UV to near-IR [55][56][57]59,60]. The spectra of the multicolored sidebands can also be tuned in the broadband spectral range by adjusting the cross-angle of the two pump beams or simply by replacing the nonlinear media [59,60].…”
Section: Introductionmentioning
confidence: 83%
“…Recently, four-wave mixing (FWM) has been studied as new method for the generation of ultrashort pulses, including few-cycle pulses, with a spectral range from deep-UV (DUV) to mid-IR [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Among these results, the multicolored laser pulses that can be generated using cascaded four-wave mixing (CFWM) in transparent bulk materials are particularly attractive, due to their ultra-broadband spectral range, large wavelength tunable range and compact configurations [54][55][56][57][58][59][60][61][62][63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations